SODIUM ALUMINATE IN CASTING PAINTS - O. S. Komarov; B. M. Nemenjonok; E. V. Rozenberg; T. D. Komarova (Литьë и металлургия, 2016)
Comparative researches showed that sodium aluminate can be successfully used as a modifying addition into the foundry paints on the basis disthen-sillimanite and lignosulfonate, as well as the binder for the chill mould paints based on graphite.